Chlorin e6-modified iron oxide nanoparticles for photothermal-photodynamic ablation of glioblastoma cells - Yao, Hongqing; Zhou, Jian-Ying (Frontiers in Bioengineering and Biotechnology, 2023)
The effective treatment of glioblastoma still remains a great challenge. We herein report the development of chlorin e6 (Ce6)-conjugated iron oxide (Fe3O4-Ce6) nanoparticles for ablation of glioblastoma cells via combining photothermal therapy (PTT) with photodynamic therapy (PDT). Ce6 was conjugated to the synthesized Fe3O4 nanoparticles to form Fe3O4-Ce6 nanoparticles displaying the optical property of Ce6. Under 808 nm laser irradiation, Fe3O4-Ce6 nanoparticles generated heat and the temperature increase did not have obvious changes after five cycles of laser irradiation, suggesting their good photothermal effect and photothermal stability. In addition, 660 nm laser irradiation of Fe3O4-Ce6 nanoparticles produced singlet oxygen ( 1 O2) to mediate PDT. The Fe3O4-Ce6 nanoparticles without laser irradiation showed a low cytotoxicity, but they would obviously kill C6 cancer cells after laser irradiation via the combinational effect of PTT and PDT. Fe3O4-Ce6 nanoparticles thus could be used as a nanotherapeutic agent for combinational ablation of glioblastoma cells.